Analysis of Transient Characteristics of Submersible Tubular Pump During Runaway Transition - Sun, Zhuangzhuang; Yu, Jie; Tang, Fangping; Ge, Hengjun; Yuan, Haixia (Frontiers in Energy Research, 2022)
When the power failure occurs, the positive flow rate and rotational speed of the pump device gradually decrease. The speed of the unit entering the runaway condition is about -1.88 times of the initial speed, and the flow is about -1.98 times of the initial flow. In the process of the pump device changing from positive flow to reverse flow, the internal flow pattern of the pump device is chaotic. The reverse flow shock causes the increase of local pressure on the blade surface, which threatens the stability of the blade structure. The pressure at the front monitoring point of the impeller increases first and then decreases with the change of flow rate, while the pressure at the rear monitoring point of the impeller decreases rapidly at the beginning due to the decrease of impeller work capacity, and then increases first and then decreases with the change of flow rate. The pressure fluctuation of the monitoring points before and after the impeller is mainly affected by the impeller speed. The greater the speed is, the greater the pressure fluctuation is, and the pressure fluctuation decreases gradually from the shroud to the hub. The instantaneous frequency of the monitoring point before the impeller is mainly at the blade frequency. In addition to the blade frequency, the monitoring point behind the impeller is also concentrated many high frequency components, the frequency due to dynamic and static interference exists except near the wheel hub.